Underground Cable Fault Detection Using Robot - Rejith Raj; Jery Althaf; Muhammad Imthiaz (Institute of Advanced Engineering and Science, 2013)
Present trend of laying cables for various purposes is to lay underground. Companies prefer laying the cables underground because the climatic adversities don’t affect this. With advantages come challenges. There are many difficulties in laying the cables and once laid in case of any complaints, it is difficult and costly to fix it. This paper is about the robot that is designed by us which is capable of finding where the complaint lies, so the engineer can directly get the hole dug at that point and fix the issue. The basic principle of Electromagnetic Theory is employed to detect the discontinuity in the cable. Using a signal injector, a low frequency signal is passed through the wire and the induced magnetic field is used to detect the fault.DOI:http://dx.doi.org/10.11591/ijece.v3i2.1839